(untitled) (Research, Society and Development, 2020)
The structure of schools today is linked to the vision and values of the actors involved in the teaching and learning process. The mechanistic view of Taylor and Ford, with regard to the control exercised in business organizations throughout the twentieth century, opposes the organic view of modernity, present in the current teaching and learning process experienced by teachers in their work activities. The research was developed in a public institution of technical, technological and higher level with the objectives of: verifying whether the Teacher Activity Regulation (RAD) contained mechanistic characteristics of Taylorist and Fordist theories; understand the level of knowledge of teachers about the RAD and verify the contributions of the control exercised by management over the activities of teachers. The research methodology is classified as descriptive with a qualitative approach and a case study. A bibliographic survey was elaborated on the legislation that guides the teaching activity in the institution and a structured and non-disguised questionnaire was used with objective and discursive questions. It is concluded that the RAD has the standardization, division of labor and control proclaimed by Taylor and Ford, and should be improved to meet the individual aspects of the profession. It is evident that, in the search for productivity, management leaves out the organic and flexible view of contemporary society and that the instrument contributes little to the professional improvement of the teacher, to the motivation and improvement of the activities developed and, within the researched organization, is mainly used to comply with current legislation.